1996
DOI: 10.1097/00000542-199605000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Sodium Channels Are Significantly Suppressed at Clinical Concentrations of Volatile Anesthetics

Abstract: All anesthetics significantly suppressed sodium currents at clinical concentrations. This suppression occurred through at least two mechanisms: (1) a potential-independent suppression of resting or open sodium channels, and (2) a hyperpolarizing shift in the voltage-dependence of channel inactivation resulting in a potential-dependent suppression of sodium currents. The voltage-dependent interaction results in IC50 values for anesthetic suppression of sodium channels that are close to clinical concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
93
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 28 publications
6
93
0
2
Order By: Relevance
“…The effect of systemic lidocaine infusion on the MAC of volatile anesthetics is partially elucidated. The anesthetic agents suppress CNS Na + channels in a voltage-dependent manner [28]. Likewise, lidocaine action on both peripheral and central nervous systems involves blockade of Na + channels [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of systemic lidocaine infusion on the MAC of volatile anesthetics is partially elucidated. The anesthetic agents suppress CNS Na + channels in a voltage-dependent manner [28]. Likewise, lidocaine action on both peripheral and central nervous systems involves blockade of Na + channels [5].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, lidocaine action on both peripheral and central nervous systems involves blockade of Na + channels [5]. So both inhalant anesthetics and lidocaine act on voltage-gated Na + channels in the central nervous system [28] and thus their effects during general anesthesia could be additive. Lidocaine ensures pain relief on the spinal level [29], which presupposes a reduction in MAC and decreases the volatile agents demand.…”
Section: Discussionmentioning
confidence: 99%
“…Recent electrophysiological studies have shown that CNS voltage-dependent Na+ channels are sensitive to inhibition by clinically relevant concentrations of both intravenous and volatile general anaesthetics (Frenkel et al, 1993;Rehberg et al, 1996). Propofol was found to reduce Na+ channel opentime (ED50 = 20 giM) by electrophysiological recording of single Na' channels from human cerebral cortex (Frenkel & Urban, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol, as well as many other general anaesthetics, has potent potentiation and agonist effects at the GABAA receptor (see Tanelian et al, 1993). Electrophysiological studies have also implicated Na+ channels as a molecular site of action for several general anaesthetics (Frenkel et al, 1993;Rehberg et al, 1996), including propofol (Frenkel & Urban, 1991), although the pharmacological relevance of these effects has been questioned (Franks & Lieb, 1994). Recently, we found that propofol at clinically relevant concentrations inhibits veratridine-evoked increases in 22Na+ flux, intracellular free Na+ levels and Na+ channeldependent glutamate release in rat cerebrocortical synaptosomes, evidence which supports a role for Na+ channel blockade in the action of propofol (Ratnakumari & Hemmings, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian voltage-gated Na + (Na V ) channels, which mediate the upstroke of the action potential, are regulated by numerous inhaled general anesthetic agents (8)(9)(10)(11)(12)(13)(14), which generally cause inhibition. Previous work showed that inhaled general anesthetic agents, including sevoflurane, isoflurane, desflurane, and halothane, mediate inhibition by increasing the rate of Na + channel inactivation, hyperpolarizing steady-state inactivation, and slowing recovery from inactivation (11,(15)(16)(17)(18). Inhibition of presynaptic Na V channels in the spinal cord is proposed to lead to inhibition of neurotransmitter release, facilitating immobilization-one of the endpoints of general anesthesia (14,19,20).…”
mentioning
confidence: 99%